Reading (of books) outdoors: on practices, metrics and prescriptions - Cordón-García, José-Antonio; Muñoz-Rico, María (Anuario ThinkEPI, 2022)
Reading has a multiple condition subject to very different interpretations depending on the perspectives from which it is approached, but there is a general consensus about its virtues and benefits for the population in general and for the development of culture in particular. The technological changes that it has undergone in the last decade, which involve all the actors in its value chain, have added functionalities, features and modalities that considerably expand the range of available content and its forms of consumption. One can speak of a reading in the open both to designate these new practices and to name the interpretation that is made of them according to the available measurement tools. The problem arises when analyzing the step from the act of reading to the affirmation of "I have read". And this is particularly important in the case of books, assumed in the collective unconscious as the most refined expression of reading practice, because given their chronodegradable condition, in terms of memory, statements about what is read can refer to non-existent works, from the point of view of its weight and the intensity of the memory, as numerous experiences and investigations have shown. Despite everything, reading books constitutes a mobilization of essential skills, especially in the university environment, in which the book is suffering an unappealable displacement in favor of other shorter and cognitively accessible genres, such as scientific articles. For all these reasons, the necessary procedures must be activated in the university to recover the role of prescription and recommendation inherent in teaching practices, especially in the Humanities and Social Sciences, in order to arouse interest and use by students. of a genre relegated to an increasingly less consistent voluntarism.